Fault tolerant longitudinal aircraft control using non‐linear integral sliding mode. Issue 17 (1st November 2014) - Alwi, Halim; Edwards, Christopher
Abstract : This study proposes a novel non‐linear fault tolerant scheme for longitudinal control of an aircraft system, comprising an integral sliding mode control allocation scheme and a backstepping structure. In fault free conditions, the closed loop system is governed by the backstepping controller and the integral sliding mode control allocation scheme only influences the performance if faults/failures occur in the primary control surfaces. In this situation, the allocation scheme redistributes the control signals to the secondary control surfaces and the scheme is able to tolerate total failures in the primary actuator. A backstepping scheme taken from the existing literature is designed for flight path angle tracking (based on the non‐linear equations of motion) and this is used as the underlying baseline controller in nominal conditions. The efficacy of the scheme is demonstrated using a high‐fidelity aircraft benchmark model. Excellent results are obtained in the presence of plant/model uncertainty in both fault free and faulty conditions.